All Days 2009
DOI: 10.2118/121414-ms
|View full text |Cite
|
Sign up to set email alerts
|

Core Flood Investigation Into Asphaltene Deposition Tendencies in the Marrat Reservoir, South East Kuwait

Abstract: Asphaltene precipitation can have profound effects on oil production during miscible flooding, heavy oil recovery, or even primary depletion. Even though asphaltene precipitation and eventual deposition have been known to have strong effects on permeability reduction (Turta et al., 1997;Minssieux et al., 1998), quantitative analysis of the process has not been studied extensively. This paper describes experimental work conducted to study the precipitation and deposition tendencies of asphaltenes within the roc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In the experiments of Takahashi et al, a larger amount of asphaltene was left behind in the more heterogeneous carbonate core than in the more homogeneous sandstone core although no significant permeability reduction was observed. Rahmani et al also found that the asphaltene deposits were confined to sites of occluded pores, which did not result in severe damage to the reservoir.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the experiments of Takahashi et al, a larger amount of asphaltene was left behind in the more heterogeneous carbonate core than in the more homogeneous sandstone core although no significant permeability reduction was observed. Rahmani et al also found that the asphaltene deposits were confined to sites of occluded pores, which did not result in severe damage to the reservoir.…”
Section: Discussionmentioning
confidence: 96%
“…In the experiments of Takahashi et al, 98 a larger amount of asphaltene was left behind in the more heterogeneous carbonate core than in the more homogeneous sandstone core although no significant permeability reduction was observed. Rahmani et al 99 also found that the asphaltene deposits were confined to sites of occluded pores, which did not result in severe damage to the reservoir. The coupling effect of the gradual adsorption and pore blockage consequently predicts a better reservoir conductivity than single-factor models, which, on the other hand, means that the early stage of asphaltene deposition is more inconspicuous than previous predictions have suggested.…”
Section: Permeability Reduction Mechanismmentioning
confidence: 95%
“…For tight or shale cores, it is usually infeasible to identify which is the primary damage factor by the traditional steadystate measurement core flooding apparatus due to long measurement time (hours or even days) and the gauge accuracy (pressure gauge and flowmeter) [15]. According to experimental theory, permeability measurements in the laboratory can be divided into two categories: the steady-state method and unsteady-state method [16].…”
Section: Introductionmentioning
confidence: 99%
“…The formation water flows continuously on the surface of the rock sample with flow pressure P m and back pressure P b . Continuously monitor the change of the downstream pressure Pð L, tÞ until it reaches the upstream flow pressure P m P m , P 0 , PðL, tÞ, and equations (4) and (5) were used to obtain the liquid permeability K ini2 of the rock sample Close valves (8)-(17) and open special core gripper (7), intermediate vessel(6), gas pressure regulating valve(22), nitrogen gas bottle (3), and valves(15) and(16). Adjust gas pressure regulating valve(22), setup the pressure, and push the working fluid into the surface of the rock sample for approximately 5 hours (7) Close valves (8)-(17) and repeat procedures (2)-(5).The measured liquid permeability of the damaged rock sample is K CSM (8) The damage rate of working fluid to the core D CSM was calculated through equation…”
mentioning
confidence: 99%